2016
DOI: 10.1038/srep32326
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 enables conditional mutagenesis of challenging loci

Abstract: The International Knockout Mouse Consortium (IKMC) has produced a genome-wide collection of 15,000 isogenic targeting vectors for conditional mutagenesis in C57BL/6N mice. Although most of the vectors have been used successfully in murine embryonic stem (ES) cells, there remain a set of nearly two thousand genes that have failed to target even after several attempts. Recent attention has turned to the use of new genome editing technology for the generation of mutant alleles in mice. Here, we demonstrate how Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…For example, it is fairly efficient to produce knockins into the genomic ROSA26 locus in mice, while other loci are targeted less efficiently, and thus refractory to knockins. This accessibility to CRISPR/Cas9 complexes mirrors observations in mouse ES cell gene targeting technology, in which it was reported that some genes are not as efficiently targeted as others [105].…”
Section: Locus-specific Genetic Engineering Vectors In Mouse and Rat supporting
confidence: 65%
“…For example, it is fairly efficient to produce knockins into the genomic ROSA26 locus in mice, while other loci are targeted less efficiently, and thus refractory to knockins. This accessibility to CRISPR/Cas9 complexes mirrors observations in mouse ES cell gene targeting technology, in which it was reported that some genes are not as efficiently targeted as others [105].…”
Section: Locus-specific Genetic Engineering Vectors In Mouse and Rat supporting
confidence: 65%
“…more than two orders of magnitude higher than reported in previous studies (Brinster et al 1989). The CRISPR/Cas9 treatment of ES cells dramatically increased homologous recombination with DNA donors (Gennequin et al 2013; Schick et al 2016, and author’s unpublished observations). Thus, the probability that correct integration of the synthetic DNA donor molecule occurred after CRISPR/Cas9-induced chromosome break is very high and the most likely explanation for the transgene knockin in Prokr2 sequence.…”
Section: Discussionmentioning
confidence: 95%
“…The purpose of gene editing in a hiPSCs workflow may be the insertion of a specific sequence from a HDR donor template, or the deletion of a genomic sequence. Templates for HDR-mediated knockin may use donor vectors that include drug selection or fluorescent marker genes enabling the efficient isolation of targeted colonies harboring stable vector integrations [33,34]. In some cases, especially for gene therapeutic purposes, the marker gene needs to be removed.…”
Section: Gene Editing Approachmentioning
confidence: 99%